Expression of EphA2 and EphrinA‐1 in vulvar carcinomas and its relation to prognosis - Holm, R (BMJ Group, 2007)
AIMS: To examine the expression of EphA2 and EphrinA‐1 in vulvar squamous cell carcinomas and investigate their prognostic relevance. METHODS: Tumours from 224 patients with vulvar squamous cell carcinomas were investigated for expression of EphA2 and EphrinA‐1 using single and double immunostaining methods. RESULTS: High expression (strong/moderate staining intensity) of EphA2 and EphrinA‐1 was observed in 114 (51%) and 126 (56%) vulvar carcinomas, respectively. In the three cases tested using the double immunostaining method, colocalisation of EphA2 and EphrinA‐1 proteins was identified in the same neoplastic cells. High EphA2 expression was significantly correlated to high expression of EphrinA‐1 (p<0.01) and cyclin A (p<0.01), large tumour size (p = 0.03), deep invasion (p<0.01) and higher FIGO stage (p = 0.05). A correlation between high EphrinA‐1 expression and high levels of cyclin A (p<0.01) and p21 (p<0.01), deep invasion (p<0.01) and higher FIGO stage (p = 0.01) was also seen. In univariate analysis, high expression of EphrinA‐1 was associated with poor survival (p = 0.03). However, in the multivariate analysis neither EphrinA‐1 nor EphA2 were significantly correlated to survival. CONCLUSIONS: EphA2 and EphrinA‐1 were overexpressed in 51% and 56% of the vulvar squamous cell carcinomas, respectively, and high levels of EphA2 and EphrinA‐1 proteins were associated with deep tumour invasion and high FIGO stage. However, EphA2 and EphrinA‐1 were not independently associated with clinical outcome in vulvar carcinomas.